Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the solutions of the equation [tex]\(x^4 - 9x^2 + 8 = 0\)[/tex], let's use the substitution method where we let [tex]\(u = x^2\)[/tex]. This simplifies our equation into a quadratic form, as follows:
1. Substitute [tex]\(u = x^2\)[/tex]:
The equation transforms to:
[tex]\[ u^2 - 9u + 8 = 0 \][/tex]
2. Solve the quadratic equation:
The equation [tex]\(u^2 - 9u + 8 = 0\)[/tex] can be solved using the quadratic formula:
[tex]\[ u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\(a = 1\)[/tex], [tex]\(b = -9\)[/tex], and [tex]\(c = 8\)[/tex]. Plugging in these values, we get:
[tex]\[ u = \frac{-(-9) \pm \sqrt{(-9)^2 - 4 \cdot 1 \cdot 8}}{2 \cdot 1} \][/tex]
[tex]\[ u = \frac{9 \pm \sqrt{81 - 32}}{2} \][/tex]
[tex]\[ u = \frac{9 \pm \sqrt{49}}{2} \][/tex]
[tex]\[ u = \frac{9 \pm 7}{2} \][/tex]
Therefore, we have two solutions for [tex]\(u\)[/tex]:
[tex]\[ u = \frac{9 + 7}{2} = \frac{16}{2} = 8 \][/tex]
[tex]\[ u = \frac{9 - 7}{2} = \frac{2}{2} = 1 \][/tex]
3. Back-substitute [tex]\(u = x^2\)[/tex]:
We now have two equations in terms of [tex]\(x\)[/tex]:
[tex]\[ x^2 = 8 \][/tex]
[tex]\[ x^2 = 1 \][/tex]
4. Solve for [tex]\(x\)[/tex]:
For [tex]\(x^2 = 8\)[/tex]:
[tex]\[ x = \pm \sqrt{8} \][/tex]
Simplifying, we get:
[tex]\[ x = \pm 2\sqrt{2} \][/tex]
For [tex]\(x^2 = 1\)[/tex]:
[tex]\[ x = \pm \sqrt{1} \][/tex]
Simplifying, we get:
[tex]\[ x = \pm 1 \][/tex]
5. Combine all solutions:
Therefore, the complete set of solutions for the original equation [tex]\(x^4 - 9x^2 + 8 = 0\)[/tex] is:
[tex]\[ x = \pm 1, \pm 2\sqrt{2} \][/tex]
This matches the option:
[tex]\[ x = \pm 1 \text{ and } x = \pm 2\sqrt{2} \][/tex]
1. Substitute [tex]\(u = x^2\)[/tex]:
The equation transforms to:
[tex]\[ u^2 - 9u + 8 = 0 \][/tex]
2. Solve the quadratic equation:
The equation [tex]\(u^2 - 9u + 8 = 0\)[/tex] can be solved using the quadratic formula:
[tex]\[ u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
Here, [tex]\(a = 1\)[/tex], [tex]\(b = -9\)[/tex], and [tex]\(c = 8\)[/tex]. Plugging in these values, we get:
[tex]\[ u = \frac{-(-9) \pm \sqrt{(-9)^2 - 4 \cdot 1 \cdot 8}}{2 \cdot 1} \][/tex]
[tex]\[ u = \frac{9 \pm \sqrt{81 - 32}}{2} \][/tex]
[tex]\[ u = \frac{9 \pm \sqrt{49}}{2} \][/tex]
[tex]\[ u = \frac{9 \pm 7}{2} \][/tex]
Therefore, we have two solutions for [tex]\(u\)[/tex]:
[tex]\[ u = \frac{9 + 7}{2} = \frac{16}{2} = 8 \][/tex]
[tex]\[ u = \frac{9 - 7}{2} = \frac{2}{2} = 1 \][/tex]
3. Back-substitute [tex]\(u = x^2\)[/tex]:
We now have two equations in terms of [tex]\(x\)[/tex]:
[tex]\[ x^2 = 8 \][/tex]
[tex]\[ x^2 = 1 \][/tex]
4. Solve for [tex]\(x\)[/tex]:
For [tex]\(x^2 = 8\)[/tex]:
[tex]\[ x = \pm \sqrt{8} \][/tex]
Simplifying, we get:
[tex]\[ x = \pm 2\sqrt{2} \][/tex]
For [tex]\(x^2 = 1\)[/tex]:
[tex]\[ x = \pm \sqrt{1} \][/tex]
Simplifying, we get:
[tex]\[ x = \pm 1 \][/tex]
5. Combine all solutions:
Therefore, the complete set of solutions for the original equation [tex]\(x^4 - 9x^2 + 8 = 0\)[/tex] is:
[tex]\[ x = \pm 1, \pm 2\sqrt{2} \][/tex]
This matches the option:
[tex]\[ x = \pm 1 \text{ and } x = \pm 2\sqrt{2} \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.